Determination of Crizotinib in Mouse Tissues by LC-MS/MS and Its Application to a Tissue Distribution Study - Fang Zhao; Yuan Wei; Yiming Yan; Han Liu; Sitong Zhou; Bo Ren; Ruijuan Liu (International Journal of Analytical Chemistry)
Toxicity induced by crizotinib, a small-molecule tyrosine kinase inhibitor, is a significant clinical issue during treatment. A tissue distribution study is required to explore the organs affected by this molecule. In this study, a simple liquid chromatography tandem mass spectrometry method was developed and validated for the determination of crizotinib in various mouse tissues. Mouse tissue homogenates were processed by protein precipitation with methanol, and apatinib was chosen as the internal standard. The analytes were separated on a Phenomenex Kinetex C18 (50 mm × 2.1 mm, 2.6 μm) column with gradient elution using methanol and 0.3% formic acid water solution. Tandem mass spectrometric detection was conducted using multiple reaction monitoring via an electrospray ionization source in the positive mode. The monitored ion transitions were m/z 450.1 ⟶ 260.2 for crizotinib and m/z 398.2 ⟶ 212.0 for apatinib. The problem of the severe carryover effect was successfully resolved. The method was validated and applied to a tissue distribution study of crizotinib in mice, which was reported for the first time. The results of the study showed that the main target organs of crizotinib were the lung, liver, and spleen, and a high concentration of crizotinib was found in the gastrointestinal tract. This study offers a reliable method for quantifying crizotinib and provides a basis for further research on crizotinib toxicity.